EURO-ATLANTIC INTEGRATION TRENDS OF THE SOUTH CAUCASIAN STATES - TATIKIAN, Sossi (CENTRAL ASIA AND THE CAUCASUS, 2006)
After the big bang enlargements of the EU and NATO in 2004, the Southern Caucasus was recognized as an important region for the further strengthening of stability, security, and prosperity in the Euro-Atlantic space. NATO declared a shift in the geographical focus of the Euro-Atlantic Partnership. While the continuing stabilization and integration of the states in the Western Balkans remained a high priority for NATO, the Southern Caucasus and Central Asia were declared its new geographical priority. Without offering the prospect of membership, NATO committed itself to refocusing its resourc-es toward these two regions, assisting those countries willing to reform their defense institutions, launch-ing political consultations with NATO, contributing to the international fight against terrorism, and destroying the stockpiles of outdated ammunitions. While the Individual Partnership Action Plan mechanism was formally offered to all Partners at the Prague Summit of NATO/EAPC in 2002, even if it was self-evident that it was designed for the Partners in the Caucasus, Central Asia, and Moldova,PAP-DIB endorsed at the Istanbul Summit in 2004 was specifically targeted at those Partners. Central Asia and the Caucasus were put in the same basket in all the documents on the Euro-Atlantic Partnership endorsed at the Istanbul Summit of NATO/EAPC. As a follow-up to the Istanbul Summit, the Secretary General appointed Mr. Robert Simmons, his Deputy Assistant for Political Affairs and Security Policy, as his Special Representative for Central Asia and the Caucasus. At the same time, he nominated two liaison officers for each of these two regions. While the Special Representative is mandated to facilitate a political dialog with the high-level officials of the countries of both regions, also being entitled to deliver the Alliance’s political messages to the general public in his interviews and briefings, the liaison officers are authorized to deal with the practical issues of defense cooperation and reforms. The liaison officer for the Caucasus mainly resides in Tbilisi, and he frequently visits Erevan and Baku.